Prevalence of ESBL-Producing Klebsiellaisolated from Burn Wound Infections in a Tertiary Care Burn Hospital in Peshawar - Zubeda Irshad, Mahnoor Khan, Rabbia Mahboob (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Patients with burns and other skin wounds suffer from skin damage and often prolonged hospitalization which compromises their immunological protection by skin and increases the chance of infections. Klebsiellain particular, have become one of the leading causes of such infections. Of even greater concern is their ability to produce extended spectrum beta-lactamases (ESBLs), enzymes that render many antibiotics useless. This study aimed to determine the prevalence of ESBL-producing Klebsiella, among the isolates from burn wound infections and to analyze their antimicrobial susceptibility patterns. Methods: A total of 363 Klebsiella isolates were obtained from wound swabs of burn patients over a one-year period from August 2021 to July 2022 were used for identification. The ESBL production was confirmed using the combination disc method. Antimicrobial sensitivity testing was performed following CLSI guidelines. Results: Out of 363 isolates, 74% were confirmed ESBL producers. Most patients belonged to the age group of 21–30 years, and a slight male predominance was observed. ESBL-producing isolates showed very low sensitivity to third-generation cephalosporins (only 2% to cefotaxime and 4% to ceftazidime), as well as reduced susceptibility to fluoroquinolones. Carbapenems remained the most effective antibiotics, over 85% demonstrating sensitivity." Conclusion: The high prevalence of ESBL-producing Klebsiella in burn wound infections is alarming and highlights the need for strict infection control measures, routine surveillance, and rational antibiotic use in burn units. Keywords: ESBL, Klebsiella, burn wound infection, antimicrobial resistance, prevalence, carbapenem, multidrug resistance.